Pengaruh Servicescape, Social Media Marketing, Service Quality, terhadap Minat Beli Ulang di Goldmine Coffee Sunrise - Ni Putu Novi Astuti; Anak Agung Putu Agung; I Gusti Ayu Imbayani (Lembaga Pengembangan Kinerja Dosen, 2026)
This study examines the effects of servicescape, social media marketing, and service quality on repurchase intention at Goldmine Coffee Sunrise, Sanur, Denpasar, amid the increasingly competitive coffee shop industry and the shift of coffee consumption into a lifestyle-driven activity. A quantitative approach was employed using a structured questionnaire distributed to 105 customers aged ≥17 years who had purchased at least twice; the data were analyzed with SPSS through instrument testing, descriptive statistics, classical assumption tests, and multiple linear regression. The results indicate that all measurement items are valid and reliable, and the regression model meets normality, multicollinearity, and heteroskedasticity assumptions. Partially, servicescape (β = 0.261; p = 0.023), social media marketing (β = 0.602; p = 0.000), and service quality (β = 0.243; p = 0.002) have positive and significant effects on repurchase intention, with social media marketing showing the strongest contribution. Simultaneously, the three independent variables significantly influence repurchase intention (F = 94.598; p = 0.000), explaining 73.0% of the variance (Adjusted R² = 0.730). These findings imply that strengthening the physical service environment, optimizing creative and consistent social media engagement, and maintaining responsive, reliable service are pivotal strategies to enhance customers’ repurchase intention at Goldmine Coffee Sunrise.